EFEKTIVITAS SERTIFIKASI DOSEN TERHADAP KOMPETENSI DOSEN DI POLTEKKES KEMENKES BENGKULU - Eliana, Eliana (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Performance is measured based lecturer faculty workload includes the followingprincipal activities of the learning plan, implement bembelajaran process, evaluating learning,guide and train, conduct research, perform community service and perform additional tasks.One of the government's efforts to improve the competence of lecturers, starting in 2008, noperformance assessment program called Lecturer Certification lecturers. The importance ofthe program Lecturer Certification as a form of assessment of faculty performance is expectedto improve the quality of education and provide benefits that can be perceived by students asoutput in the world of education. This study aims to determine differences in the competenceof lecturers who have tersertifkasi and yet tersertifkasi in Poltekkes MoH Bengkulu 2014.This research was analytic cross-sectional study. The population in this study are all still in thepolytechnic lecturers Bengkulu MoH both JFU and JFT are 85 people, samples were takenwith total sampling technique. Data analysis was performed using univariate and bivariateindependent T test. The results showed that the majority (75.7%) lecturers alreadytersertiifikasi, most (64.9%) lecturers are aged ≥ 45 years and almost all (83.8%) lecturershave been teaching ≥ 5 years, and there was no difference the competence of lecturers arecertified with certified faculty who have both pedagogical, professional, personal and social. Itis expected that the relevant agencies to carry out monitoring and evaluation of the learningprocess both on students and lecturers.